Mutual Control of Cholinergic and Low-Threshold Spike Interneurons in the Striatum - Elghaba, Rasha; Vautrelle, Nicolas; Bracci, Enrico (Frontiers in Cellular Neuroscience, 2016)
The striatum is the largest nucleus of the basal ganglia and is crucially involved in action selection and reward processing. Cortical and thalamic inputs to the striatum are processed by local networks in which several classes of interneurons play an important, but still poorly understood role. Here we investigated the interactions between cholinergic and low-threshold spike (LTS) interneurons. LTS interneurons were hyperpolarised by co-application of muscarinic and nicotinic receptor antagonists (atropine and mecamylamine, respectively). Mecamylamine alone also caused hyperpolarisations, while atropine alone caused depolarisations and increased firing. LTS interneurons were also under control of tonic GABA, as application of the GABAA receptor antagonist picrotoxin caused depolarisations and increased firing. Frequency of spontaneous GABAergic events in LTS interneurons was increased by co-application of atropine and mecamylamine or by atropine alone, but reduced by mecamylamine alone. In the presence of picrotoxin and tetrodotoxin, atropine and mecamylamine depolarised the LTS interneurons. We concluded that part of the excitatory effects of tonic acetylcholine (ACh) on LTS interneurons were due to cholinergic modulation of tonic GABA. We then studied the influence of LTS interneurons on cholinergic interneurons. Application of antagonists of somatostatin or neuropeptide Y receptors or of an inhibitor of nitric oxide synthase (L-NAME) did not cause detectable effects in cholinergic interneurons. However, prolonged synchronised depolarisations of LTS interneurons (elicited with optogenetics tools) caused slow-onset depolarisations in cholinergic interneurons, which were often accompanied by strong action potential firing and were fully abolished by L-NAME. Thus, a mutual excitatory influence exists between LTS and cholinergic interneurons in the striatum, providing an opportunity for sustained activation of the two cell types. This activation may endow the striatal microcircuits with the ability to enter a high acetylcholine/high nitric oxide regime when adequately triggered by external excitatory stimuli to these interneurons.